PENGARUH DUKUNGAN SOSIAL TERHADAP EFIKASI DIRI WANITA TUNA SUSILA MENGIKUTI REHABILITASI SOSIAL DI PANTI SOSIAL PELAYANAN WANITA (WANODYATAMA) SURAKARTA - Mila Puspita Arum; Triyono Triyono (Academic Journal of Psychology and Counseling, 2021)
One difficulty to eradicate prostitution in Indonesia is due to the low self-efficacy of female prostitutes. This research aims to examine the effect of social support towards the self-efficacy of female prostitutes joining social rehabilitation in the women’s service house of Wanodyatama Surakarta. This research employed quantitative method with socal support and self-efficacy scales. Data testing was done by used validity test (used try-out), reliability test, normality test, and linearity test. Simple linear regression analysis was done for data analysis. There were 31 persons included in the sample through total sampling technique since the subject was less than 100 persons. The results show the significant value of t obtained (5% = 78.401) which is higher than t table (1.69913) at the significant level of 0.05. It can be concluded that Hα is accepted. It implies that there is significant effect of social support towards the self-efficacy of female prostitutes